Spatial distribution visualization of PWM continuous variable-rate spray - Wei, Deng; Huang, Yanbo; Chunjiang, Zhao; Xiu, Wang; Jinglong, Liu (International Journal of Agricultural and Biological Engineering, 2013)
Abstract: Pesticide application is a dynamic spatial distribution process, in which spray liquid should be able to cover the targets with desired thickness and uniformity. Therefore, it is important to study the 2-D and 3-D (dimensional) spray distribution to evaluate spraying quality. The curve-surface generation methods in Excel were used to establish 1-D, 2-D, and 3-D graphics of variable-rate spray distribution in order to characterize the space distribution of the variable-rate spray. The 1-D, 2-D, and 3-D distribution graphs of Pulse-Width Modulation (PWM)-based continuous variable-rate spray were developed to provide a tool to analyze the distribution characteristics of the spray. The 1-D graph showed that the spray distribution concentrated toward the center of the spray field with the decreased flow-rate. The 2-D graph showed that the spray distribution always spread as the shape of Normal Probability Distribution with the change of the flow-rate. The 3-D graph showed that the spray distribution tended to be uniform when the sprayer travelled forward at the appropriate speed. This study indicated that the visualization method could be directly used for analysis and comparison of different variable-rate spray distributions from different experimental conditions and measuring methods. Keywords: spray distribution, pulse width modulation (PWM), variable-rate spray, distribution visualization DOI: 10.3965/j.ijabe.20130604.001 Citation: Deng W, Huang Y B, Zhao C J, Wang X, Liu J L. Spatial distribution visualization of PWM continuous variable-rate spray. Int J Agric & Biol Eng, 2013; 6(4): 1－8.